Clinical Volunteering through the Pandemic: An Experience from Final Year Medical Students in Nigeria - Aderounmu, Boluwatife; Odedara, Ayodele (International Journal of Medical Students, 2021)
First reported in Wuhan, China, the Coronavirus Disease 2019 (COVID-19) spread globally causing it to be declared a pandemic. Its widespread nature necessitated lockdown measures in world nations including Nigeria. Instituted lockdown measures led to the closure of tertiary institutions in the country. Medical schools were designated as high-risk institutions due to possible exposure to COVID-19. With no measures for virtual learning, academic activities were put on hold, thus posing a challenge for medical students. The author in this article discovered an opportunity to learn in the midst of the lockdown by volunteering at a healthcare institution. In the course of volunteering, the author had symptoms highly suggestive of COVID-19. However, it was not confirmed by a Polymerase Chain Reaction test due to obstacles surrounding COVID-19 testing in the country. Following recovery, the author participated in risk communication to members of his community to curtail the spread and dispel the myths concerning COVID-19. While the volunteering experience provided an opportunity to continue medical education, it is vital that there be a shift in the Nigerian educational system to one where academic activities are not disrupted by pandemics or other situations that might not permit on-site learning.